Adopted Children with the Legal Status of Biological Children: Implications for Inheritance Rights - Eka Mahargiani; Itsna Ummahatul Izza; Eko Sariyekti (Yayasan Azhar Amanaa Yogyakarta, 2025)
In Islam, the tradition of adoption has been known since the pre-Islamic period and later regulated by Sharia to maintain the principles of justice and public interest. However, currently there are adopted children who hold the status of biological children, and this has become something that needs to be examined. The purpose of this research is to examine the status of adopted children who are treated like biological children in terms of inheritance, both based on positive law in Indonesia and according to Islamic law. The method used in this research employs a normative juridical approach. The research is descriptive qualitative and conducted through literature study. The data sources consist of primary data such as the Compilation of Islamic Law article 171 letter h, article 209 paragraph 2, scholars' opinions, as well as Law No. 35 of 2014 jo. Law No. 23 of 2002 and Government Regulation No. 54 of 2007. Data collection techniques include document review and literature study, while data analysis is carried out through the stages of collection, processing, analysis, and interpretation to obtain accurate conclusions. The results of this study explain that adopted children do not have the right to their adoptive parents' inheritance due to the absence of blood relation, but they can still receive part of the inheritance through gifts, wills, or obligatory wills with a maximum limit of one-third of the total inheritance. In Positive Law, according to Law No. 35 of 2014 concerning Child Protection, the inheritance issue of adopted children who have the status of biological children is not explained in detail, but it is stated that adopted children are treated like biological children and have equal rights to care, education, and protection.